1965
DOI: 10.1083/jcb.26.2.395
|View full text |Cite
|
Sign up to set email alerts
|

THE PHOTOSYNTHETIC APPARATUS OF RHODOSPIRILLUM MOLISCHIANUM

Abstract: By varying thc light intensity and tcmpcrature during growth it is possible to obtain cultures of Rhodospirillum molischianum in which the spccific bacteriochlorophyll contents differ by as much as fivcfold. We used such cultures to compare the changes in the electron microscopic appearance of the cells with thc changes in thc amount and bacteriochlorophyll content of chromatophorc matcrial isolated from cell extracts. Thc cells contained a variable number of internal membranes which arc invaginations of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1966
1966
2010
2010

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…However, Fig. 1A is in agreement with the spectra observed by Gibbs et al (19). This shift of absorption is associated with a modification in the LH2 polypeptides synthesized through differential expression of the various puc operons.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…However, Fig. 1A is in agreement with the spectra observed by Gibbs et al (19). This shift of absorption is associated with a modification in the LH2 polypeptides synthesized through differential expression of the various puc operons.…”
Section: Resultssupporting
confidence: 82%
“…In many species of bacteria, adaptation to low light intensities involves changing the proportions of core complexes and LH2. Extra LH2 are synthesized to increase the effective reaction center absorption cross section (18,19). This modification is associated with the formation of large para-crystalline domains of LH2 in the photosynthetic membranes (20).…”
mentioning
confidence: 99%
“…Intracytoplasmic membranes occur as stacks (Figs. 2 and 3) as in the brown colored Rhodospirillum species, R.fulvum, R. molischianum, R.photometricum (Gibbs et al, 1965) and the species of the genus Ectothiorhodospira, E. shaposhnikovii (Cherni et al, 1969), E. mobilis (Trfiper, 1968;Remsen et al, 1968;Holt et al, 1968) and E.…”
Section: E Halochloris Is Bipolarly Flagellated Possessing Twomentioning
confidence: 99%
“…Such observations have led Holt, Conti, and Fuller (1966b) to conclude that the formation of the photosynthetic apparatus is an inverse function of light intensity which correlates with the proposal by Cohen-Bazire and Kunisawa (1963), that the amount of pigment in cells of R. rubrum is inversely related to light intensity and oxygen tension. Gibbs, Sistrom, and Worden (1965) showed that a paradox existed between elec tron microscopic observations and analytical results regarding the amount of bacteriochlorophyll and chromatophore material in the cell.…”
Section: Environmental Effectsmentioning
confidence: 99%
“…The several mechanisms that have been proposed to account for the origin of chromatophores can be summarized as follows: (1) formation of a reticulum by infoldings of the cytoplasmic membrane into the cytoplasm as observed in Rhodo spirillum rubrum (Cohen-Bazire and Runisawa, 1963); (2) direct forma tion by invagination of the cytoplasmic membrane from which discrete, uniform vesicles are formed in: R. rubrum (Cohen-Bazire and Kunisawa, 1963;Boatman, 1964;Oda and Horio, 1964); and in Rhodopseudomonas spheroides (Gibson, 1965); (3) by binary fission as indicated by the "dumb-bell" shaped chromatophores of R. spheroides (Gibson, 1965); and (4) fragmentation of the intracytoplasmic membranes as in Rhodospirillum rubrum (Hickman and Frenkel, 1965b;Holt and Marr, 1965b). The photosynthetic apparatus is described as a lamellar array rather than a vesicular system in Rhodospirillum molischianum (Drews, 1960;Giesbrecht and Drews, 1962;Hickman and Frenkel, 1965a;Gibbs, Sistrom, and Worden, 1965); Rhodomicrobium vannielli (Boatman and Douglas, 1961;Vatter, Douglas, and Wolfe, 1959); and Rhodopseudomonas viridis (Drews and Giesbrecht, 1965;1966).…”
Section: Chromatophoresmentioning
confidence: 99%